ESTIMASI MATRIKS ASAL TUJUAN PERJALANAN MENGGUNAKAN MODEL GRAVITY DENGAN FUNGSI HAMBATAN EKSPONENSIAL-NEGATIF DI KOTA SURAKARTA - Hendarwati Pamungkas; Syafi'i Syafi'i; Setiono Setiono (Program Studi Teknik Sipil FT UNS, 2014)
Transportation problems such as congestion, noise and air pollution, accidents, delay and other problems happen because the bigger movement tofulfill life necessities which is more complex. It can be solved by using good transportation planning. MAT is a two-dimensional matrix containsinformation about the amount of movements inter location (zones) within a certain area. MAT can provide a detail indication of the movementsneed, so MAT plays important role in the study of transportation planning and management. This research was conducted in Surakarta by dividingthe study area into 65 zones with 51 internal zones and 14 external zones. In analyzing of road network, it includes arterial roads and collectorroads. The aims of this research are to determine the magnitude of Origin Destination Matrix estimation of the data traffic using applicationEMME / 3 at Surakarta in the year of 2013, and also the research is intended to know the level of validation of traffic flow using the result ofmodeling of traffic flow observation in the field. In this research to estimate the MAT in the plan, it use the limitation Gravity Model productionand attraction movement. This research also uses Matlab software application to get the value of the parameter ?with exponential-negative barrierfunction. The traffic volume value was obtained by imposing new matrix and incorporating current observation (traffic count) in the road network.Test validation using determination coefficient (R2 ). The value of parameter ?by using application software Matlab is -0,00042. The result of thecalculation by using EMME/3 shows the total number of estimation of movement Surakarta in the year of 2013 is 37298,98 smp/jam withlevel of validation (R2 ) is 0,78. This case shows the value (R2 ) of this study fall into the category of high validation, has 78% similarity to theoriginal condition in Surakarta city streets.